Urinary incontinence in young gymnastics athletes: a scoping review - Higounenc, A.; Carvalhais, A.; Vieira, Á.; Lopes, S. (Sports, 2025)
Background/Objectives: Urinary incontinence (UI) is increasingly reported among young nulliparous women, especially those engaged in high-impact sports. This may increase the risk of developing stress urinary incontinence (SUI) later in life. This scoping review aims to synthesise current evidence on UI in gymnasts, identify the gymnastics modalities with the highest prevalence of UI, and examine the outcomes measures and interventions considered for UI.